(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The Nigerian National Policy on Education advocates for mother-tongue instruction in early childhood learning, a principle aligned with global standards for linguistic justice and educational equity. However, the implementation of Mother-Tongue Based Multilingual Education (MTB-MLE) remains profoundly ineffective, leading to a pervasive disconnect between policy rhetoric and classroom reality. This persistent failure exacerbates educational inequalities, hinders cognitive development, and marginalizes Nigeria’s vast linguistic heritage. This conceptual paper argues that the current challenges—including a lack of political will, inadequate resources, ethno-linguistic politicization, and a misconceived policy framework—stem from a fundamental lack of a coherent, context-specific theoretical and operational model. Moving beyond mere critique, this study proposes a novel, multi-dimensional framework for implementing MTB-MLE in the Nigerian context. Drawing on theoretical foundations of linguistic human rights (Skutnabb-Kangas, 2000) and language economics (Grin, 2003), the framework is built on four interdependent pillars: (1) a multi-tiered language selection protocol that categorizes languages based on regional dominance and vitality; (2) a integrated curriculum model that strategically bridges the mother tongue with English; (3) a sustainable teacher training and material development ecosystem; and (4) a participatory governance structure involving communities, policymakers, and educators. The paper concludes that for MTB-MLE to transition from policy phantom to praxis, it must be reimagined not as a cultural annex but as the central pillar of a just, effective, and nationally inclusive educational strategy for Nigeria.